2022
DOI: 10.3390/molecules27051676
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Biological Activities and In Silico Analysis of Essential Oils of Three Endemic Prangos Species from Turkey

Abstract: In this study, the essential oils (EOs) obtained from three endemic Prangos species from Turkey (P. heyniae, P. meliocarpoides var. meliocarpoides, and P. uechtritzii) were studied for their chemical composition and biological activities. β-Bisabolenal (12.2%) and caryophyllene oxide (7.9%) were the principal components of P. heyniae EO, while P. meliocarpoides EO contained sabinene (16.7%) and p-cymene (13.2%), and P. uechtritzii EO contained p-cymene (24.6%) and caryophyllene oxide (19.6%), as the most abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 47 publications
(60 reference statements)
1
17
0
Order By: Relevance
“…The aerial parts of the Prangos species were collected during Summer 2020 from Central Anatolia Region of Turkey. The information of the collection area was reported in our earlier paper [ 28 ]. Voucher specimens were deposited at the herbarium of Selcuk University, Science Faculty (Voucher numbers: EY-3039, EY-2998, and EY-3023 for P. heyniae , P. meliocarpoides var.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aerial parts of the Prangos species were collected during Summer 2020 from Central Anatolia Region of Turkey. The information of the collection area was reported in our earlier paper [ 28 ]. Voucher specimens were deposited at the herbarium of Selcuk University, Science Faculty (Voucher numbers: EY-3039, EY-2998, and EY-3023 for P. heyniae , P. meliocarpoides var.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study by Sevin et al [ 27 ] examined the erectile function of root extract of P. uechtritzii as well as P. heyniae , and the authors reported that oxypeucedanin was the most active coumarin. In our earlier paper [ 28 ], the chemical characterization and biological activities of the essential oils of three Prangos species were reported. Although many studies have examined the phytochemical composition and bioactivity of different Prangos species, the three species examined here still need to be evaluated and confirmed by scientists.…”
Section: Introductionmentioning
confidence: 99%
“…[14] In addition to various bioactivity studies of the genus such as antibacterial, antioxidant, antiviral, and cytotoxic activities, anticholinesterase activities of the different Prangos species have also been investigated. [15,16] Coumarins are the major groups among the metabolites occurring in the genus and in addition to many biological activities, they also exhibit AChE and BChE inhibitory activities relevant to neurodegenerative diseases. [17] Polyacetylenes are mostly distributed in the families of Apiaceae, Araliaceae, and Asteraceae.…”
Section: Introductionmentioning
confidence: 99%
“…[21] The phytochemical investigations of P. uechtritzii are limited to GC analysis of volatile oil obtained from the aerial parts and fruits. [15,16] Antibacterial, antifungal, antioxidant, and enzyme inhibitory studies are the bioactivity studies conducted with P. uechtritzii. [15,16] However, to the best of our knowledge, the roots of the plant have not been investigated for their detailed phytochemical content, also for anticholinesterase properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation